Penerapan Metode Design Thinking untuk Perancangan UI/UX Sistem E-Marketplace Berbasis Website - Muhammad Ridwan Sulistyono; Agus Setiawan; Nuryanto Nuryanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
E-Marketplace is an application that allows users to enjoy a shopping experience with a minimalist design. A systematic manufacturing process using design thinking empathize, define, ideate, prototype and test methodologies. The author hopes to create an ideal website for various marketing platforms. The design thinking method can also work smoothly if UI and UX (User Interface and User Experience) can be created. Using the usability test method as a prototype reference and using the Google Form to determine the best design for the TOP 5 marketplaces and using Preview Figma to solicit different opinions at the Emphatize stage by collecting data from 105 Shopee, Lazada, Blili, Bukalapak and Tokopedia users to use Google's market solutions. The purpose of this research is that this prototype can be accepted by the community, especially active market users. After going through different stages, the final result of this research is the creation of a homepage according to the components of the system design. Received user test data About 99% of the 105 data collected, of which 54.3% women and 45.7% men used the marketing platform and presented their assumptions about the header design obtained from the screen design which received 58.1% of the 105 users who chose SHOPEE. In the final stage, FGD (Forum Group Discussion) and expert judgment were carried out to determine whether the prototype created was ideal and able to compete in the virtual world market. can be interpreted as a conclusion that this prototype can be accepted in the community, considering that it still needs significant improvement and development according to user feedback.